EDUKASI PEMBUATAN SABUN CAIR CUCI PIRING PADA PASIEN SKIZOFRENIA DI RSJ SURAKARTA - Fuadi, Ahmad M; Lestari, Ayu; Ath-Tariq, Muhammad Arhab; Fitri, Zada Almira (Prosiding University Research Colloquium, 2024)
The types and characteristics of mental disorders are very diverse, one of which is often treated is schizophrenia. At the Surakarta Regional Mental Hospital (RSJD) the number of schizophrenia patients is relatively large. It is estimated that more than 90% of schizophrenia patients experience hallucinations. To minimize the impact of hallucinations, appropriate treatment is needed. Group activity therapy is a therapeutic modality which is an effort to facilitate nurses or psychotherapists with a number of patients at the same time. The aim of this service activity is to provide provisions to patients and provide therapeutic activities to increase the level of hallucinations in patients. The educational activity of making liquid dishwashing soap is an alternative to fulfill this activity. The activity was carried out at RSJD Surakarta.